2021
DOI: 10.1136/bcr-2021-243465
|View full text |Cite
|
Sign up to set email alerts
|

Painless spontaneous haemoperitoneum secondary to a uterine leiomyoma/fibroid: unusual presentation of a life-threatening differential

Abstract: This is a case of a 47-year-old woman with a spontaneous haemoperitoneum secondary to uterine leiomyomas (fibroids), an important differential diagnosis in patients with uterine fibroids and hypovolaemic shock. Uterine fibroids are very common in women of reproductive age, yet little is taught about their potential to cause hypovolaemic shock. Although it is a rare complication, given the prevalence of fibroids, it is important to bear this life-threatening differential in mind to optimise the care for these w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is reported that ULM is the indication for all hysterectomies performed. This common ULM, due to its invasion and metastasis different from other malignant tumors, brings a variety of harm to women, such as menstrual abnormalities, recurrent pregnancy loss, gynecological diseases, pelvic pressure and so on [ 1 ]. Although the occurrence and development of leiomyoma have been deeply studied, the etiology and pathogenesis of leiomyoma remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ULM is the indication for all hysterectomies performed. This common ULM, due to its invasion and metastasis different from other malignant tumors, brings a variety of harm to women, such as menstrual abnormalities, recurrent pregnancy loss, gynecological diseases, pelvic pressure and so on [ 1 ]. Although the occurrence and development of leiomyoma have been deeply studied, the etiology and pathogenesis of leiomyoma remain unclear.…”
Section: Introductionmentioning
confidence: 99%